Exceptionally preserved arthropodan microfossils from the Middle Ordovician Winneshiek Lagerstätte, Iowa, USA. (11th August 2017) - Nowak, Hendrik; Harvey, Thomas H. P.; Liu, Huaibao P.; McKay, Robert M.; Servais, Thomas
Abstract : The Middle Ordovician (Darriwilian) Winneshiek Shale from Winneshiek County, Iowa, USA, hosts a Konservat‐Lagerstätte that has yielded a diverse fauna including soft‐bodied fossils. The shale is rich in organic content; in particular, algal material and fragmentary cuticular remains. Palynological acid treatment alongside modified, low‐manipulation processing enables the extraction of these 'small carbonaceous fossils' (SCFs) from the matrix, allowing a more detailed view of their morphology. Together these methods have yielded exceptionally well‐preserved crustacean‐type setae and a population of distinctive microfossils which we identify as the feeding appendages of a small‐bodied arthropod. We present two hypotheses for their identity: as either pancrustacean mandibles, or euchelicerate coxae. Overall, the detailed topological similarities and implied functional equivalence to the coxae of xiphosurid chelicerates, in particular, outweigh the resemblance to certain branchiopodan and hexapodan mandibles. In turn, however, the restricted size range and lack of associated limb or carapace fragments pose a taphonomic conundrum, suggesting an extreme biostratinomic bias. By comparison with previously described arthropodan SCFs from the Cambrian of Canada, the Winneshiek fossils extend the geographic, palaeoenvironmental and temporal range of this taphonomic window and provide a complementary tool for reconstructing the diversity and ecology of the Winneshiek biota.